2020
DOI: 10.26226/morressier.5f0c7d3058e581e69b05d182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corporate Board Diversity and Performance: Nonlinear Dynamics.

Abstract: In 2018, California became the first state in the US to require gender diversity on public corporate boards in the state, and since then board gender diversity is a hot debate in the US. To provide timely evidence on this issue, we investigate the relation between corporate board diversity and financial performance and how shareholders' board gender diversity proposal impacts firm performance in the US. Consistent with the resource dependence theory and social identity theory, our findings show that the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…If firms become dominated by female leadership, gains of leadership diversity could theoretically be lost. Xie et al [36] suggest that the positive effects of diversity may peak at a turning point. Beyond this, the negative aspects of diversity-increased conflicts, miscommunication, and mistrust-will dominate.…”
Section: Leadership Gender Diversity and Firm Performance: Limits To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…If firms become dominated by female leadership, gains of leadership diversity could theoretically be lost. Xie et al [36] suggest that the positive effects of diversity may peak at a turning point. Beyond this, the negative aspects of diversity-increased conflicts, miscommunication, and mistrust-will dominate.…”
Section: Leadership Gender Diversity and Firm Performance: Limits To ...mentioning
confidence: 99%
“…This would imply that the relationship between female leadership participation and firm performance is curvilinear rather than linear. While much of the literature has assumed a linear relationship [18], some studies have found evidence of a non-linear relationship for some diversity attributes [7,35,36].…”
Section: Leadership Gender Diversity and Firm Performance: Limits To ...mentioning
confidence: 99%